2010
DOI: 10.1117/12.867727
|View full text |Cite
|
Sign up to set email alerts
|

Densification and residual stress induced by CO 2 laser-based mitigation of SiO 2 surfaces

Abstract: Knowing the ultimate surface morphology resulting from CO 2 laser mitigation of induced laser damage is important both for determining adequate treatment protocols, and for preventing deleterious intensification upon subsequent illumination of downstream optics. Physical effects such as evaporation, viscous flow and densification can strongly affect the final morphology of the treated site. Evaporation is a strong function of temperature and will play a leading role in determining pit shapes when the evaporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The resulting change of the density leads to a densification of glass material and thus to a quasiablation. 29 This effect occurs already before reaching the evaporation temperature on the surface. The second mechanism is the evaporation of material.…”
Section: B Laser Beam Figuringmentioning
confidence: 99%
“…The resulting change of the density leads to a densification of glass material and thus to a quasiablation. 29 This effect occurs already before reaching the evaporation temperature on the surface. The second mechanism is the evaporation of material.…”
Section: B Laser Beam Figuringmentioning
confidence: 99%
“…11 Since our simulation does not take matter ejection into account, its results are not expected to be valid for T > 2100 K. Analogous fused silica behavior has been recently reported at similar temperatures. 15 Since several different thermal conductivities have been published, we show a comparison with our resulting thermal conductivity in Fig. 3(a).…”
mentioning
confidence: 99%
“…If the cooling rate of the materials in the irradiated region after damage mitigation is effectively slowed, the structures of these materials that they reached high temperatures may gradually change to the states corresponding to low thermodynamic temperatures during the decrease of the temperature. Feit et al reported [16] a linear ramp down of the CO 2 laser power following the damage mitigation can effectively suppress the plastic deformation induced by the quenching, and the more gradual the cooling, the smaller the plastic deformation. A linear decrease of CO 2 laser power from 19.7 watt to 8.7 watt with different exposure times was performed following the damage mitigation to minimize the residual stress.…”
Section: Resultsmentioning
confidence: 99%
“…The melt zone of mitigated site can not completely relax the strained material over the time that is shorter compared to structural relaxation time, and a structure corresponding to high temperature is frozen at higher density, so the melt zone is plastically deformed. After collective cooling of the fused silica sample, the thermal expansion of the irradiated region vanishes and the plastic deformation of the melt zone with higher density remains, and the central melt zone undergoes tensile stress [14][15][16].…”
Section: Methodsmentioning
confidence: 99%